Fraud Diamond: An Assessment Of Its Elements On Fraudulent Financial Reporting Of Companies Listed On The Indonesia Stock Exchange - Samirah Dunakhir; Mukhammad Idrus; Sahade Sahade (Jurnal Office, 2022)
The research aimed to analyse the effect of fraud diamond components on the occurrence of fraudulent financial statements. The components of fraud diamond which include financial stability, external pressure, personal financial need, financial target, nature of industry, ineffective monitoring, auditor change, audit opinion and directior change were independent variables that were suspected to affect the fraudulent financial statement in the company. Population in this research was all financial statements of food and beverage companies listed on the Indonesia stock exchange which have been audited and published. Samples were financial statements of food and beverage companies period 2012-2016 taken through purposive sampling as many as ten companies. Data analysis techniques used were classical assumption test, hypothesis test (Test R2, Test F and Test T) and multiple linear regression analysis test. The results of this research indicated that personal financial need variables measured by the ratio of stock composition owned by the company (OSHIP) affect the occurrence of fraudulent financial statement. While the financial stability, external pressure, financial target, nature of industry, ineffective monitoring, auditor change, audit opinion and director change have no effect on the occurrence of fraudulent financial statement.